Principios jurídicos y principios bioéticos. Separación, vinculación, integración - Luis Tinant, Eduardo (2012)
Legal and bioethical principles. Separation, connection, integrationThis work is intended to establish relationships between legal and bioethical principles especially when bioethical principles complement and enrich legal ones in order to solve a specific case. Prior author’s contributions on bioethical principles as legal topics and legal bioethics creation in terms of a branch of bioethics which studies legal regulations as well as legal implementation and scope of bioethical problems are referred, making a critical reflection on growing and fruitful relationships between bioethics and law. An Interdisciplinary integration proposed in order to realize cooperation between both fields rejecting a separation or mere connection is suggested: «hetero integration», an integrating system produced by development of common and related principles. The article concludes stating that law structure is a «textual» subject not just involve on the writing of the law but capable to be analyzed from a social sense point of view, conferred to different manifestation of this discipline together with several social practices; a path warning by the need to broad theoretical-practical frameworks in order to move towards the interdisciplinarity taking into account bioethics from its foundations.